Transpedicular Endoscopic Surgery for Highly Downmigrated L5-S1 Disc Herniation - Guntram Krzok (Case Reports in Medicine)
Endoscopic surgery for highly downmigrated disc herniation at level L5-S1 is a challenging technique. Most surgeons prefer the interlaminar access because of the special anatomy of the L5-S1 disc level, i.e., narrow neuroforamen and large interlaminar window. Transforaminal access to the neuroforamen L5-S1 is difficult in cases with high iliac crest. Here, the access to the highly downmigrated disc herniation with the recently reported technique of transpedicular endoscopic surgery by Krzok et al. was described. In 3 cases with highly downmigrated disc herniation of L5-S1, the sequester was removed successfully through the bone hole of S1 pedicle. This technique is demanding for experienced endoscopic surgeons.